Nicardipine Inhibits Breast Cancer Migration via Nrf2/HO-1 Axis and Matrix Metalloproteinase-9 Regulation - Chen, Yen-Chang; Chen, Jia-Hong; Tsai, Cheng-Fang; Wu, Chen-Teng; Wu, Miao-Hsiang; Chang, Pei-Chun; Yeh, Wei-Lan (Frontiers in Pharmacology, 2021)
Background: Metastasis represents an advanced stage of cancers, and matrix metalloproteinases are critical regulators. Calcium signal is crucial for appropriate cell behaviors. The efficacy and effects of calcium channel blockers in treating cancers are individually differ from each other. Here, we attempt to investigate the effects of nicardipine, a FDA-approved calcium channel blocker, in advanced breast cancers. Methods: We analyzed the influence of nicardipine on the colony-forming ability of triple negative breast cancer cell lines. Using cell culture inserts, cell migration was also examined. The expression of regulatory proteins was evaluated by real-time PCR, Western blot, and ELISA. Results: We have confirmed that nicardipine inhibits the breast cancer cells migration and colony formation. In addition, we also revealed that nicardipine increases the Nrf2 and HO-1 expression. The inhibition of HO-1 abrogates nicardipine-reduced matrix metalloproteinase-9 expression. Moreover, the end products of HO-1, namely, CO, Fe2+, and biliverdin (will converted to bilirubin), also decreases the expression of matrix metalloproteinase-9. Conclusion: These findings suggest that nicardipine-mediated matrix metalloproteinase-9 reduction is regulated by Nrf2/HO-1 axis and its catalytic end products. Therefore, nicardipine may be a potential candidate for repurposing against advanced breast cancers.